First branchial cleft sinus presenting with cholesteatoma and external auditory canal atresia - Yalçin, S; Karlidag, T; Kaygusuz, I; Demirbag, E (Elsevier Sci Ireland Ltd, 2003)
First branchial cleft abnormalities are rare. They may involve the external auditory canal and middle ear. We describe a 6-year-old girt with congenital external auditory canal atresia, microtia, and cholesteatoma of mastoid and middle ear in addition to the first branchial cleft abnormalities. Clinical features of the patient are briefly described and the embryological relationship between first branchial cleft anomaly and external auditory canal atresia is discussed. The surgical management of these lesions may be performed, both the complete excision of the sinus and reconstructive otologic surgery. (C) 2003 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: first branchial cleft anomaly; external auditory canal atresia; cholesteatoma